Regularization inertial proximal point algorithm for unconstrained vector convex optimization problems - Nguen, Byong (Ukrains’kyi Matematychnyi Zhurnal, 2008)
The purpose of this paper is to investigate an iterative regularization method of proximal point type for solving ill posed vector convex optimization problems in Hilbert spaces. Applications to the convex feasibility problems and the problem of common fixed points for nonexpansive potential mappings are also given.